Back Cover: Cyclometalated N‐Heterocyclic Carbene Platinum(II) Complexes with Bridging Pyrazolates: Enhanced Photophysical Properties of Binuclear Blue Emitters (ChemPhotoChem 4/2017). Issue 4 (5th April 2017) - Pinter, P.; Unger, Y.; Strassner, T.
Abstract : The Back Cover picture shows bimetallic platinum complexes, created by the combination of two specifically designed ligands, that show outstanding photophysical properties. The distance between the Pt atoms controls the color and the decay time, leading to a sky blue phosphorescent emitter with enhanced performance. More information can be found in the Communication by T. Strassner et al. onpage 113 in Issue 4, 2017 (DOI:10.1002/cptc.201600065 ).